Representasi Hatarakisugi pada Tokoh Aoyama Takashi dalam Film Chotto Ima Kara Shigoto Yamete Kuru karya Izuru Narushima - Kitai, Taro (Vocational College of Diponegoro University, 2024)
This research is titled